Efficient, Hydrophobic, and Weather-Resistant Radiative Cooling Paints with Silicone-Based Binders - Barber, Emily; Feng, Dudong; Fang, Ziqi; Carne, Daniel; Gonzalez, Orlando Rivera; Lee, Won-June; Vansal, Navdeep; Raykova, Katherine; Ruan, Xiulin (ACS applied optical materials, 2025)
Radiative cooling technology has gained significant interest, in large part due to the discovery of passive subambient cooling without any external energy input. These technologies, while pertinent in the areas of climate change and heating, ventilation, and air conditioning (HVAC) efficiency, have encountered unique issues, including dampening of their effects over time due to soiling and UV weathering. This study advances passive radiative cooling paint technology through the incorporation of MP-101, a silicone-based binder developed by SDC Inc., into hBN-based radiative cooling paints. The introduction of MP-101 enhances the durability of these paints, addressing issues related to contamination and ultraviolet radiation. The newly formulated paint exhibits an ultrahigh solar reflectance of 97.8%, an average temperature reduction of 1.97 °C in West Lafayette, IN, USA, and a hydrophobic surface with a static contact angle of 142° without any topcoats, implying improved self-cleaning capabilities compared to previous hBN formulations. Comprehensive investigations into abrasive properties, pigment loading percentages, cooling performance, and UV exposure demonstrated the optimization of the formula’s durability and cooling performance. The self-cleaning feature not only preserves optical properties over time but also extends the applicability of the paint to diverse settings, including buildings, transportation, and outdoor electronic systems, with reduced maintenance requirements and the highest known reflectance of hydrophobic radiative cooling materials.